Flexible glass flat-fibre chips and femtosecond laser inscription as enabling technologies for photonic devices - Riziotis, Christos; Kalli, Kyriacos; Markos, Christos; Posporis, Andreas; Koutsides, Charalambos; Webb, Andrew Simon; Holmes, Christopher H.; Gates, James C.; Sahu, Jayanta Kumar S; Smith, Peter George R (My University, 2014)
The potential of a new class of multifunctional photonic circuits is demonstrated by femtosecond laser micro-machining and inscription of micro-optical structures, such as ring and disk resonators, Mach-Zehnder interferometers, and microfluidic devices, in a flexible flat-fibre chip. Additional filling of surface channels with functional materials is employed towards sensing applications. Furthermore, direct write femtosecond-laser inscribed Bragg gratings were written in the Ge-doped core of flat-fibre enabling a number of relevant applications. The flat-fibre platform offers a unique degree of freedom by allowing surface and sub-surface devices to be integrated onto an a single optical chip with the potential for straightforward incorporation into integrated photonic circuits or optofluidic devices.
Keywords: Femtosecond laser inscription; Flat fibre; Integrated optics; Microfluidics; Optical fibres; Sensors